2020
DOI: 10.1111/ics.12668
|View full text |Cite
|
Sign up to set email alerts
|

A validated photonumeric scale for infraorbital dark circles and its application in evaluating the efficacy of a cosmetic treatment product in a split‐face randomized clinical trial

Abstract: Objective As a result of their complex aetiology and periodicity, dark circles are difficult to characterize and measure, with current assessment techniques relying on specialist equipment, image analysis or proprietary grading scales. There is therefore a need to develop and validate a photonumeric scale for assessing infraorbital dark circles, which can provide an objective and consumer relevant tool for evaluating this condition and the efficacy of treatment products and procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In principle, the decrease of b * leads to a deeper color of the copigmentation solution, thereby weakening light reflection and decreasing the L * value. , As graphed in Figure G–J, with the concentration increase of each lignan, the L * and b * values gradually decreased, while the values of a * and Δ E * showed an increasing trend. Δ E * was usually used to detect changes in food color, and a change equal to or higher than 1.0 was regarded as visually detected by people’s eyes . Actually, the Δ E * values were equal to or higher than 1.0 in this study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In principle, the decrease of b * leads to a deeper color of the copigmentation solution, thereby weakening light reflection and decreasing the L * value. , As graphed in Figure G–J, with the concentration increase of each lignan, the L * and b * values gradually decreased, while the values of a * and Δ E * showed an increasing trend. Δ E * was usually used to detect changes in food color, and a change equal to or higher than 1.0 was regarded as visually detected by people’s eyes . Actually, the Δ E * values were equal to or higher than 1.0 in this study.…”
Section: Resultssupporting
confidence: 90%
“…ΔE* was usually used to detect changes in food color, and a change equal to or higher than 1.0 was regarded as visually detected by people's eyes. 40 Actually, the ΔE* values were equal to or higher than 1.0 in this study. These results suggested that six lignans had a favorable influence on copigmentation, where schisandrin B was most active due to its highest values of negative b* (1.32 ± 0.02) and ΔE* (2.59 ± 0.11) at a concentration of 1.5 × 10 −5 M. These findings were consistent with the above experimental results, and a similar phenomenon was also described by Gonzaĺez-Manzano, 38 who investigated the catechin-induced copigmentation.…”
Section: ■ Materials and Methodsmentioning
confidence: 44%
“…As the score increases, the intensity of the dark circles also increases. 10 Fitzpatrick’s classification was used for assessment of periorbital wrinkling: degree of elastosis from 1 point to 9 points. While 1 point indicates that the wrinkling condition is fine, 9 points indicates that the wrinkling condition is the most intense.…”
Section: Methodsmentioning
confidence: 99%
“…An institutional review board (IRB) approved, open‐label, 12 week, clinical study was conducted. Female subjects located in New Jersey, USA ( n = 40) between 35 and 60 years old, FSTs I–VI, with moderate‐to‐severe under‐eye dark circles (score 4–8 based on a photonumeric scale for infraorbital dark circles), 24 moderate under‐eye puffiness (score of 4–6 based on the modified Griffiths scale), 25 and mild‐to‐moderate fine lines (score of 3–6 based on the modified Griffiths scale), and dull skin in the periorbital eye area were recruited into the study. Subjects were excluded if they were nursing, pregnant, or planning a pregnancy, had used topical retinoids or topical eye cream/serums within the past 7 days prior to baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Investigator clinical grading was performed at baseline, weeks 4, 8, and 12. A validated photonumeric scale for infraorbital dark circles based on the principles of the modified Griffiths scale was utilized, 24 while the modified Griffiths scale was utilized to evaluate under‐eye puffiness, and overall appearance of the periorbital eye area. (Supplementary Section for further analysis).…”
Section: Methodsmentioning
confidence: 99%